Control de ingresos del Gobierno Autónomo Descentralizado Municipal del cantón Babahoyo durante el periodo 2022. - Palma Montoya, Palma Montoya Anggery Anabella (2024)
This study will focus on direct evaluation with the objective of reviewing and understanding the reforms implemented in operations within the decentralized autonomous government of Babahoyo Canton, how income-related values are created. In this case study, it is important to analyze the budget items to understand how they were established and the various reforms implemented during the study period. For the execution of an operating model that allows adequate planning by the decentralized autonomous government of the Babahoyo Canton, the level of efficiency and effectiveness increases to prioritize the needs of the population and improve public spending decision-making, because it becomes possible. This investigation is totally feasible since it will be carried out in collaboration with the same director responsible for the operations of the Decentralized Autonomous Government of the Babahoyo Canton. In this way, the GAD budget can be defined as a tool for planning and managing functions that will allow future activities carried out in public institutions to use all resources productively, with methods to achieve the proposed objectives that will benefit community.